Measurement of the Ellipsometric Parameters of Thin Graphene Layers in the Extreme Ultraviolet. Issue 1 (1st December 2022) - Zuppella, P; Samparisi, F; Frassetto, F; Rigato, V; Campostrini, M; Poletto, L
Abstract: A reflection polarimeter for the XUV (30 – 100 eV) spectral range realized with three ruthenium optics has been designed, developed and tested. The instrument is conceived to be an insertable device, maintaining unaltered the XUV beam propagation direction. For energies greater than ∼55 eV, ruthenium permits to obtain a higher throughput than the one obtainable with gold optics. We propose a procedure to measure properties of graphene: the method uses a reference sample in place of one ruthenium mirror, as consequence the measure does not depend on the optical properties of the two remaining ruthenium mirrors. With this instrument we have performed ellipsometric measurements on thin graphene layers in the 15 – 30 eV spectral range.